PENGARUH MODEL DISCOVERY LEARNING DENGAN METODE EKSPERIMEN TERHADAP HASIL BELAJAR - Lestari, Eka Suci; Boy, Bonefasius Yanwar; Walukow, Auldry F. (Universitas Cenderawasih, 2024)
Research has been carried out with the aim of knowing, enhancing, correlating, and influencing learning using the discovery learning model (X) with the experimental method on the results of liquid pressure learning in students (Y). This type of research is quantitative research with Pre-Experimental Design research methods and One-Group Pretest-Posttest Design types. The population of this study were all eighth grade students of Muhammadiyah Middle School Jayapura. The sampling technique used is Nonprobability sampling by means of purposive sampling, and samples of VIIIB class students totaling 34 students. This study uses 2 instruments, namely discovery learning model questionnaire instruments and student learning outcomes test instruments on the subject of liquid pressure. To determine the increase in learning outcomes of students used N-gain analysis. To find out the relationship between the discovery learning model (X) and learning outcomes (Y) students used simple correlation analysis of Pearson Product Moment using SPSS 16.0 software and to find out the effect between X variable to Y used simple regression analysis using SPSS version software 16,0. The results of research and data processing obtained there is an increase in student learning outcomes of 0.75 which is included in the high category. Asymp Value. Sig. (2-tailed) = 0.04 <0.05, H0 is rejected, meaning that there is a relationship between variables X and Y. Pearson Correlation value = 0.355 is interpreted to have a sufficient relationship. The value of R Square = 0.126 means that there is an influence of X on Y of 12.6%. Sig value. 0.00 <0.05, H0 is rejected, meaning that there is an influence between variables X and Y. The regression equation is Y = 46,861 + 0.396 X.